Case report: Organ donation after euthanasia for psychiatric suffering: some of the practical and ethical lessons Martijn taught us - van Dijk, Nathalie; de Jongh, Wim; Stärcke, Paulan; Shaw, David; Bollen, Jan; van Mook, Walther (Frontiers in Psychiatry, 2024)
Euthanasia in psychiatric patients presents unique challenges, especially when combined with organ donation. In this article, the hurdles psychiatric patients might encounter after expressing their wish for organ donation after euthanasia, are discussed and illustrated by the case of Martijn, a 45-year-old psychiatric patient who altruistically donated his organs after euthanasia. Hospital and physician-related factors, including caution in determination of mental capacity, consideration of conflicting interests, and healthcare staff stress are discussed as impediments to organ donation after euthanasia (ODE) in psychiatric patients. The primary objective of this article is to raise awareness among psychiatrists regarding the fact that although the combination of euthanasia and organ donation is an uncommonly performed procedure, it is frequently requested by psychiatric patients. In conclusion, the article advocates for a nuanced approach, respecting patients' altruistic wishes while at the same time addressing challenges associated with ODE in psychiatric suffering. Where possible, and within the current medical, ethical and legal boundaries, the importance of facilitating organ donation without unnecessarily prolonging the suffering of competent psychiatric patients seeking euthanasia is emphasized. The topic calls, for example, for further qualitative research to understand the stakeholders' perspectives to determine the perceived possibilities on the one hand and boundaries on the other.